A case study of bacterial leaf blight disease of rice in Sungai Besar, Selangor / Ain Najwa Ameerah An-Nabiha Baharudin Ali - Baharudin Ali, Ain Najwa Ameerah An-Nabiha (Faculty of Plantation and Agrotechnology, 2017)
Paddy is common crop in Asia and because paddy is sources of food as well as source of income. However, there are several diseases attacked paddy cultivation caused the yield production decreases which are bacterial leaf blight, bacterial sheath blight and brown spot. Among this disease, bacterial leaf blight caused by Xanthomonas pv.oryzae pathogen is considered to be most serious disease that attacked the paddy plants. Bacterial leaf blights appears on leaves of young plants at near tip and margin that show pale green to grey green coloured. The objective of this case study are to measure incidence and severity as well as the factors that relate to bacterial leaf blight disease in several area in Sungai Besar, Selangor. Currently, for this season 1/2016 paddy cultivation in Sungai Besar area having disease problem especially bacterial leaf blight that has long time not affected by disease. Therefore, several areas in Sungai Besar, Selangor were surveyed early August 2016, for bacterial leaf blight disease. Result indicated that from three fields, Field A has the highest mean of disease severity with 63.11% whereas incidence is 68.83%. Second highest mean of disease severity is Field B with 46.22% whereas incidence was 33.44%. Next, the lowest mean of disease severity is Field C with 36.89% whereas incident occurs was 32.34%. These disease severity and incidence were affected by fertilizer application and environmental factors such as weather, rainfall, humidity and temperature. In conclusion, the objective has been achieved regarding to measure the incidence and severity of bacterial leaf blight is severe in Field A, but not too severe in Field B and C.